Estimation of time since death from morphological changes in red blood cells of human cadaver: An autopsy-based study - Anand, Aditya; Banerjee, K K; Kohli, Anil; Kumar Arora, Vinod (Journal of Indian Academy of Forensic Medicine, 2021)
Estimation of time since death continues to be a significant problem for forensic pathologists. It plays an essential role in medico legal cases because forensic experts are often asked to assess death time in the investigation. Estimating time since death by studying biochemical changes in blood, CSF, intraocular fluids and other morphological changes in red blood cells is relatively unexplored; very few studies have been done on this topic. A descriptive cross-sectional study was planned to study the morphological changes in Red Blood Cells (RBC) obtained from a refrigerated human cadaver at different postmortem intervals. A total of 210 cases were included in the present study, irrespective of sex. We found that up to 3 hours of post mortem interval morphology of RBCs was normal. In RBC first morphological change observed was irregular and crenated margins at a post mortem interval of 4 hours. We observed complete lysis of RBC at a post mortem interval of 11 hours earliest. Post mortem interval can be estimated by observing morphological changes in a human corpse’s blood cells with some degree of accuracy.